PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PADANG (JURNAL ECONOMICA : Research of Economic And Economic Education, 2013)
Human resources is a factor that determines the success of an organization in achieving a goal. Efforts should be made to improve the performance of employees, among others, with good leadership and motivation in the workplace is high. Attainable goal of this study was to determine, influence or leadership and motivation on employee performance in Perusahaan Daerah Air Minum (PDAM) Kota Padang. Object of study the research is employee to Perusahaan Daerah Air Minum (PDAM) Kota Padang with population a mean 113 people employee. This study used a sample of 85 people selected by random cluster sampling technique. Analysis technique used is path analysis. Obtained in a partial amount of leadership influence on job motivation employee amount 0,231 with significant meaning hypotheses 0,034 positive and significant effect between leadership variables to job motivation, obtained in a number of partial influence of leadership on employee performance is equal to 0.291 with a mean of 0.007 significant positive and significant effect hypothesis between the variables of leadership on employee performance, obtained in a number of partial influence of work motivation on the performance of employees is equal to 0.212 with a mean of 0.045 significant positive and significant effect hypothesis between the variables of job motivation on employee performance and obtained in a number of partial influence of leadership and job motivation on employee performance with a value of 7.692 with a significant F value of 0.001 means that a positive and significant effect hypothesis between the variables of leadership and job motivation on employee performance. To achieve high employee performance and motivation of the employees' leadership at the Perusahaan Daerah Air Minum (PDAM) Kota Padang must be improved.